Non-targeted Colonization by the Endomycorrhizal Fungus, Serendipita vermifera, in Three Weeds Typically Co-occurring with Switchgrass - Ray, Prasun; Guo, Yingqing; Kolape, Jaydeep; Craven, Kelly D. (Frontiers in Plant Science, 2018)
Serendipita vermifera (=Sebacina vermifera; isolate MAFF305830) is a mycorrhizal fungus originally isolated from the roots of an Australian orchid that we have previously shown to be beneficial in enhancing biomass yield and drought tolerance in switchgrass, an important bioenergy crop for cellulosic ethanol production in the United States. However, almost nothing is known about how this root-associated fungus proliferates and grows through the soil matrix. Such information is critical to evaluate the possibility of non-target effects, such as unintended spread to weedy plants growing near a colonized switchgrass plant in a field environment. A microcosm experiment was conducted to study movement of vegetative mycelia of S. vermifera between intentially-inoculated switchgrass (Panicum virgatum L.) and nearby weeds. We constructed size-exclusion microcosms to test three different common weeds, large crabgrass (Digitaria sanguinalis L.), Texas panicum (Panicum texanum L.), and Broadleaf signalgrass (Brachiaria platyphylla L.), all species that typically co-occur in Southern Oklahoma and potentially compete with switchgrass. We report that such colonization of non-target plants by S. vermifera can indeed occur, seemingly via co-mingled root systems. As a consequence of colonization, significant enhancement of growth was noted in signalgrass, while a mild increase (albeit not significant) was evident in crabgrass. Migration of the fungus seems unlikely in root-free bulk soil, as we failed to see transmission when the roots were kept separate. This research is the first documentation of non-targeted colonization of this unique root symbiotic fungus and highlights the need for such assessments prior to deployment of biological organisms in the field.